(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
The article contains the findings of research on the historical approach used to build the mausoleum of Ismail Samani and the Kalyan minaret. It is revealed that calcium sulfate is mainly used in the compositions of the solutions. These historical solutions are also modified with organic and mineral additives. Based on chemical, differential-thermal analysis (DTA), reed analysis revealed that reed ash, chickpea flour and lime were used in these solutions. Considering the analytic findings, we synthesized the combinations of modified compounds based on local gypsum. The composition along with technology for obtaining converted solutions for the instauration of old city’s architectural landmarks of Bukhara have been developed. The developed composition of the modified solution is put into practice. The research demonstrates that the structure and strength of the modified gypsum-based solution are virtually identical to the structure of the mortar used in national architectural monuments.